Calmodulin Enhances Cryptochrome Binding to INAD in Drosophila Photoreceptors - Mazzotta, Gabriella Margherita; Bellanda, Massimo; Minervini, Giovanni; Damulewicz, Milena; Cusumano, Paola; Aufiero, Simona; Stefani, Monica; Zambelli, Barbara; Mammi, Stefano; Costa, Rodolfo; Tosatto, Silvio C. E. (Frontiers in Molecular Neuroscience, 2018)
Light is the main environmental stimulus that synchronizes the endogenous timekeeping systems in most terrestrial organisms. Drosophila cryptochrome (dCRY) is a light-responsive flavoprotein that detects changes in light intensity and wavelength around dawn and dusk. We have previously shown that dCRY acts through INAD (Inactivation No Afterpotential D) in a light-dependent manner on the Signalplex, a multiprotein complex that includes visual-signaling molecules, suggesting a role for dCRY in fly vision. Here, we predict and demonstrate a novel Ca2+-dependent interaction between dCRY and calmodulin (CaM). Through in yeast two hybrid, Co-IP, NMR, and calorimetric analyses we were able to identify and characterize a CaM binding motif in the dCRY N-terminus. Similarly, we also detailed the CaM binding site of the scaffold protein INAD and demonstrated that CaM bridges dCRY and INAD to form a ternary complex in vivo. Our results suggest a process whereby a rapid dCRY light response stimulates an interaction with INAD, which can be further consolidated by a novel mechanism regulated by CaM.